Verbal, Visual, and Gestural Expressions of Social Criticism for Anti-Social Behavior of Indonesian People in an A Mild Video Commercial - John Calvin Mulyanto (Institute of Research and Community Outreach - Petra Christian University, 2022)
Video commercials are an essential tool in advertising nowadays. Many Products right now use video commercials as their main tool to advertise their product; cigarettes are not an exception. However, since they cannot display the products in the commercials due to the rules in Indonesia, cigarette companies use creative methods to advertise their product. Instead, the companies use verbal, visual and gestural expressions to deliver the messages of what the companies want to say. In this thesis, I aim to discover how social criticism of the anti-social behavior of Indonesian people is portrayed through verbal, visual and gestural expressions in A mild video commercials. I used Multimodal Discourse Analysis, social criticism, and anti-social behavior theory to help analyze the data. Next, I analyze each piece of data in accordance with each mode and connect it with the social criticism message. Based on my analysis, I found out that the message of the social criticism in the video commercials can be seen through the linguistic mode, visual mode, and gestural mode. In conclusion, using social criticism in video commercials is an effective way for companies to give messages to viewers.